Gauging the upshot of liquid medicaments on surface roughness and stability of color in pit and fissure sealant - In vitro study - C H Chandana Krishna Shree; G K Pallavi Urs; H R Pooja; Andrea Natalia Mascarenhas; Anisha Jenny; Priya Nagar (Wolters Kluwer Medknow Publications, 2022)
Background: With esthetics in demand among pediatric patients, maintenance, color stability and surface roughness has become a vital tool to gauge the success of dental restorations. Aim: The aim of the study is to evaluate the effect of liquid medicaments on color stability and surface roughness of three different pit and fissure sealants. Materials and Methods: Twenty-seven premolars indicated for orthodontic extraction were selected and grouped based on sealants applied (n = 9) into three groups, namely PF Seal (PF), Conseal F (C), and Helioseal (H), which were subdivided into antibiotic, analgesic, and multivitamin based on medicament (n = 3). Selected sealant was placed on teeth, respectively, and immediate color stability and surface roughness (Ra) were gauged using Adobe Photoshop software and profilometer, respectively. Sealant-placed teeth were subjected to liquid formulations for 2 min for every 8 h duration. On 7th and 14th day, the color stability and Ra values were re-assessed. The analysis of outcomes was carried out using Statistical Package for the Social Sciences for Windows Version 22.0 Released 2013. Armonk, NY: IBM Corp. Results: Intergroup analysis showed that the color stability was better with Conseal F compared to PF seal and Helioseal F and the mean Ra values showed a significant increase from baseline to 14th-day measurement. Intragroup analysis revealed the highest surface roughness with antibiotic group compared to other medicaments. Conclusion: The prolonged use of liquid drug formulations such as analgesics, antibiotics, and multivitamins has shown to have a negative effect on the stability of color and surface roughness of the sealants.